Transnational social work : opportunities and challenges of a global profession - Bartley, Allen; Beddoe, Liz, 1956- (Policy Press, 2018)
"This unique book provides an international comparison of labour markets, migrant professionals and immigration policies, and their interaction in relation to social work. Case studies based on the latest research from the UK, Ireland, Canada, New Zealand and Australia allow readers to make critical comparisons and gain understanding of the global nature of the social work profession. Detailed analysis covers the opportunities and challenges presented by labour market mobility, the implications for social justice and discussion of the experiences and perceptions of transnational social workers. Essential reading for social work educators, academics and professionals, this book will also inform the development of relevant policy, professional, and educational responses to the phenomenon of transnational social work mobility."--